2021
DOI: 10.3389/fneur.2021.666596
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy vs. Thrombolysis in Pre-stroke Dependent Patients With Large Vessel Occlusions Within the Anterior Circulation

Abstract: Background: In the past few years, several randomized trials have clearly shown that endovascular treatment (ET) in addition to intravenous thrombolysis (IVT) is superior to IVT alone in patients with proximal cerebral arterial occlusions. However, the effectiveness of ET in pre-stroke dependent patients (modified Rankin Scale ≥3) is uncertain.Methods: Using our prospectively obtained stroke database, we analyzed the impact of pre-stroke dependence on the rates of poor outcome (discharge mRS 5–6), in-hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Indeed, we also found that patients with pre-morbid disability were older, more frequently women, and had higher baseline NIHSS scores compared with non-disabled patients, corroborating previous reports 32 36. The trend towards lower mortality seen in patients with pre-morbid disability who received EVT, compared with those who only received MM in the two studies that included this control group,25 26 also suggests that EVT is unlikely to be driving the higher mortality of these patients in the other observational studies. Of note, among the included studies, only two reported the cause of death in patients with pre-morbid disability, with ICH and ischemic stroke progression being the most frequent causes 14 15…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, we also found that patients with pre-morbid disability were older, more frequently women, and had higher baseline NIHSS scores compared with non-disabled patients, corroborating previous reports 32 36. The trend towards lower mortality seen in patients with pre-morbid disability who received EVT, compared with those who only received MM in the two studies that included this control group,25 26 also suggests that EVT is unlikely to be driving the higher mortality of these patients in the other observational studies. Of note, among the included studies, only two reported the cause of death in patients with pre-morbid disability, with ICH and ischemic stroke progression being the most frequent causes 14 15…”
Section: Discussionsupporting
confidence: 89%
“…Ten studies compared outcomes between patients with versus without pre-morbid stroke disability treated with EVT 14–24. We found two studies comparing patients with pre-morbid disability treated with EVT to pre-morbidly disabled patients receiving medical management alone 25 26. One study included only patients with disability and did not have a control group,27 and one study included only patients older than 80 years 20.…”
Section: Resultsmentioning
confidence: 99%
“…Six conference abstracts were excluded ( 9 – 14 ). Two articles focusing on the comparison of PSD patients undergoing EVT vs. standard medical treatment (SMT) were excluded ( 3 , 4 ). Two articles that failed to compare PSD and PSI groups were also excluded ( 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, most randomized controlled trials (RCTs) and real-world research limited investigation of patients with a pre-stroke modified Rankin scale (mRS) score of 0–1, and those with a score of ≥2 were largely excluded ( 2 ). There are studies showing that even with a higher mRS score, pre-stroke dependent (PSD) patients may also benefit from EVT when compared with best medical therapy ( 3 , 4 ). It is less clear whether these patients achieve similar safety and efficacy as pre-stroke independent patients (PSI) after EVT.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have investigated the impact of EVT or bridging therapy compared to IVT alone in patients with PSD. For example, Kastrup et al ( 29 ) reported that EVT improved clinical outcome at the time of discharge, avoided poor outcome, and caused smaller infarcts compared to IVT in PSD patients. However, more randomized trials and comparative studies that adopt this study design are needed to shed light on whether this group of PSD patients should be recommended for EVT.…”
Section: Discussionmentioning
confidence: 99%